The management of the surgical complications of HELLP syndrome - Wilson, SG (Ann R Coll Surg Engl, 2014)
INTRODUCTION: Complications from HELLP (Haemolysis, Elevated Liver enzymes and Low Platelet) syndrome may present as an emergency to any surgeon. We review the ten-year experience of a tertiary hepatobiliary centre managing HELLP patients. Three selected cases are described to highlight our management strategy and a systematic review of the recent literature is presented. METHODS: All patients with HELLP syndrome were identified from a prospectively maintained database and their details collated. Subsequently, a detailed search of PubMed was carried out to identify all case series of HELLP syndrome in the literature in the English language since 1999. RESULTS: On review of 1,002 cases, 10 patients were identified with surgical complications of HELLP syndrome. Seven of these patients had a significant liver injury. Only three of these required surgical intervention for liver injury although four other patients required surgical intervention for other complications. There was no maternal mortality in this series. Review of the literature identified 49 cases in 31 publications. The management approaches of these patients were compared with ours. CONCLUSIONS: We have presented a large series of patients with surgical complications resulting from HELLP syndrome managed without maternal mortality. This review has confirmed that haemodynamically stable patients with HELLP syndrome associated hepatic rupture can be conservatively treated successfully. However, in unstable patients, perihepatic packing and transfer to a specialist liver unit is recommended.